Analisis Rasio Keuangan Untuk Menilai Kesehatan Perusahaan Telekomunikasi Di Indonesia - Nurul Hidayah; Aris Munandar; Nurul Huda (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The purpose of this study is to analyze the Financial Ratios to assess the health of telecommunications companies in Indonesia. The type of research used by researchers in this study is descriptive research. The research instrument used is a list of tables containing variable indicators Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turn Over (TATO), Return On Asset (ROA) and Net Profit Margin (NPM) of PT. Telekomunikasi Indonesia, Tbk, PT. Indosat, Tbk and PT. XL Axiata, Tbk for 5 years, namely from 2019 to 2023. The type of quantitative data and data taken in this study is secondary data. The population used in this study is the financial statements of 18 telecommunications companies listed on the Indonesia Stock Exchange. The sample in this study is the financial statements of 3 telecommunications companies listed on the IDX with the sampling technique used is purposive sampling. Data collection techniques used in this study are documentation techniques and literature studies. Data analysis uses ratio analysis and uses one-tailed t-test analysis (One Sample t-test) with the help of SPSS version 26. Based on the results of descriptive analysis and statistical tests on the financial ratios of the last five years (2019–2023) the three largest telecommunications companies in Indonesia are in an unhealthy condition.